2011
DOI: 10.1051/parasite/2011181039
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, biology and taxonomy ofDendritobilharzia loossiSkrjabin, 1924 (Trematoda: Bilharziellidae), a parasite ofPelecanus onocrotalus(Pelecanidae) andAnas plathyrinchos(Anatidae)

Abstract: Life cycles of Dendritobilharzia loossi Skrjabin, 1924, a parasite of waterbirds, and its morphobiological traits are studied and described. Mollusks Anisus spirorbis, the infection rate of which in natural environments reaches 1.3-1.9%, were recorded as intermediate hosts under conditions of Uzbekistan. The development of this trematode in intermediate and definitive hosts lasts for 26 and 15 days, respectively. Diagnostic traits of the trematodes during all stages of their ontogeny are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…are specific to a single snail species or a group of closely-related congeners (Kock, 2001;Rudolfova et al, 2005;Brant and Loker, 2009;Jouet et al, 2009), and experimental and genetic confirmation that a species of Trichobilharzia can infect multiple genera of snails within a family has yet to be achieved. There is a report of an avian schistosome Dendritobilhariza pulverulenta (Cheatum, 1941) found in both Gyraulus (North America, New Zealand) and Anisus (Europe) snails but the genetic identity of the worms from Anisus have not been confirmed as D. pulverulenta, since there exists more than one species (Khalifa, 1976;Vusse, 1980;Brant et al, 2011) and Dendritobilhariza loossi has been found experimentally to use Anisus vortex in Europe (Akramova et al, 2011). Snail surveys carried out in Europe (Rudolfova et al, 2005;Jouet et al, 2009b) and Africa (Appleton and Brackenbury, 1998;Laamrani et al, 2005), have failed to recover any Trichobilharzia spp.…”
Section: Discussionmentioning
confidence: 99%
“…are specific to a single snail species or a group of closely-related congeners (Kock, 2001;Rudolfova et al, 2005;Brant and Loker, 2009;Jouet et al, 2009), and experimental and genetic confirmation that a species of Trichobilharzia can infect multiple genera of snails within a family has yet to be achieved. There is a report of an avian schistosome Dendritobilhariza pulverulenta (Cheatum, 1941) found in both Gyraulus (North America, New Zealand) and Anisus (Europe) snails but the genetic identity of the worms from Anisus have not been confirmed as D. pulverulenta, since there exists more than one species (Khalifa, 1976;Vusse, 1980;Brant et al, 2011) and Dendritobilhariza loossi has been found experimentally to use Anisus vortex in Europe (Akramova et al, 2011). Snail surveys carried out in Europe (Rudolfova et al, 2005;Jouet et al, 2009b) and Africa (Appleton and Brackenbury, 1998;Laamrani et al, 2005), have failed to recover any Trichobilharzia spp.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term observations have shown that parthenitae of Schistosomatidae and Bilharziellidae representatives parasitize exclusively the hepatopancreatic gland of molluscs (Azimov, 1975(Azimov, , 1986Shakarboev, 2009;Akramova, 2011;Akramova et al, 2007Akramova et al, , 2010Akramova et al, a, b, 2011Horak et al, 2002). However, data on changes in the structural organization of the mollusc liver under the influence of parthenitae and cercariae of above mentioned trematodes are extremely fragmentary and insufficient.…”
Section: Introductionmentioning
confidence: 99%